Auditoria regular realizada a las instituciones educativas Rio Verde Bajo, Instituto Buenavista, Jose Maria Cordoba, Rio Verde Alto, Instituto Genova, San Vicente de Paul, Antonio Nariño, Gabriela Mistral, La Popa, Luis Arango Cardona, Pedacito De Cielo Alvaro Uribe Velez, Santa Teresita, Ramon Mesa Londoño y Hojas Anchas en la vigencia 2013 (2014)
Regular audit performed at educational institutions of the Municipalities of BUENAVISTA, CORDOBA, GENOVA, LA TEBAIDA, QUIMBAYA Y CIRCACIA for the term 2013. She was executed according to the parameters established in the Territorial New Audit Guide adopted by the CONTRALORIA QUINDÍO (CGQ). This process is conducted in the following phases: Planning: in which knowledge is made the client and establishing the list of activities, the second phase, execution, carried out the activities stated in the previous phase, which are composed of the lines results Management, Accounting, Budget and contractual on the basis of the information given by each control point through the Integrated Audit (SIA) and Procurement information System visible (COVI) as a result of this process is identified some inconsistencies, which were rinsed, the last phase, in which report is made to the opinion whose content is the opinion on the reasonableness of the and financial evaluation of the Administrative management, budgetary, contractual.